Principles into Policy: Assessing the Impact of Conservation Principles in Local Planning Policy. (3rd July 2019) - Chitty, Gill; Smith, Claire
ABSTRACT: The arc of policy change in heritage conservation in England – from the 1967 Civic Amenities Act to the National Planning Policy Framework 2018 – spans significant shifts in the underpinning principles supporting conservation policies. While national policies can be interpreted as inflections of changing policy frameworks enacted in international and European arenas, the interplay is complex and causal relationships may be impossible to demonstrate conclusively. This paper takes the instance of English Heritage (now Historic England)'s Conservation Principles, Policies and Guidance for the sustainable management of the historic environment (2008) and considers its international hinterland and legacy. While it has no formal status in the heritage protection or planning system in England, this research examines its sustained presence in local heritage planning policy. An examination of local heritage strategy documents shows that Conservation Principles, and the body of early 21st-century European and international thought that it reflects, are embedded in current practice in local authority policy-making. This impact is notable in the context of an English statutory planning and heritage protection system largely unchanged for 30 years, and attests to the agency of innovative international conservation principles despite the inertia of national heritage reform.